Fabrication of ultralong ceria nanobelts via a coordination polymer precursor method. (8th February 2018) - Li, Yuan; Zou, Honghong; Qiao, Zhiwei; Liao, Yuanyuan; Wang, Lei; Zhong, Shengliang
Abstract : Ultralong cerium-based coordination polymer (CP) nanobelts have been successfully synthesized through a facile solvothemal approach. After calcination in air and being loaded 1 wt% Pt, the catalyst showed satisfactory activity of catalytic reduction of p -nitrophenol. Abstract : Ultralong cerium-based coordination polymer (Ce-CP) nanobelts have been prepared from benzene-1, 3-dicarboxylic acid (1, 3-H2 BDC) and Ce(NO3 )3 via a facile solvothermal method, employing a cheap and non-toxic mixture of ethanol and water as solvent. The products were well characterized and analyzed. The nanobelts are dozens of micrometers in length, 50–200 nm in width, and 20–40 nm in thickness. Reaction parameters such as molar ratio of reactants, reaction temperature and time of preparation were also investigated in detail. CeO2 nanobelts were obtained after calcining the CP nanobelts in air at 400 °C for 4 h. The activity of the catalytic reduction of p -nitrophenol by the 1 wt% Pt loaded CeO2 nanobelts was investigated. Furthermore, other rare earth-based CP micro/nano structures were also prepared using this method.